Reactualization of Intellectualism in Classical Islamic Thought in Indonesia: Comparative Study of Muhammadiyah and Nahdlatul Ulama post Reformatio - Rusli, Ris’an; Darmawan, Candra; Rudin, Toha; Ibrahim, Ahlam Binti (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT The findings of the re-actualization of classical Islamic intellectualism in Indonesia are found in the Muhammadiyah and Nahdlatul Ulama organizations, namely: First, the field of divinity, which includes discussion of God and His attributes and the relationship of the universe with Him. Second, the field of morals (ethics), which includes discussions about humans and their behavior; human relationship with God, human relationship with each other and human relationship with the universe. Third, the field of physics; includes a discussion about the nature of its growth and development, and so forth.